Correlation between cone penetration test and bearing capacity for shallow foundation - Ahmad, Mazlan (2007)
The Cone Penetration Test (CPT) is a simple and versatile test that is becoming more popular in Malaysia for soft clay and fine to medium coarse sand. It can be used as a direct method to determine the soil bearing capacity for a foundation. Analyses were carried out on the CPT data from local project site based on the published correlation and. Data were grouped into cohesive and non cohesive. Based on the results, it is observed that the current published correlations are not suitable to be used in Malaysia. Meyerhof’s Bearing Capacity and Schmertmann’s equations were used to obtain the estimated bearing capacity. These figures were then plotted on the graphs and the best fit lines are obtained. Two correlations had been evaluated and presented. These correlations represent cohesive and non cohesive soil respectively. From the two correlations, it can be concluded that Schmertmann’s correlation gives a much higher value compared with bearing capacity calculated using Meyerhof’s. However it shall be noted that the lack of data prevents a better correlation from being produced. A correlation had been proposed in the study to predict the soil bearing capacity value based on the tip resistance. However these correlations are not to be used in practice due to its limitation of data. The published correlations are not suitable to estimate the soil bearing capacity for shallow foundation for soil under study Bearing Capacity correlation for cohesive and non cohesive soils proposed by Schmertmann is likely to overestimate the actual bearing capacity values. The correlation is not appropriate to be used in Malaysia.